Effects of soil management on biodiversity of Hemiptera, Heteroptera in vineyards of Valtellina (Northern Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
Research on the biodiversity of Hemiptera was carried out in 1997-1999 in two viticultura! areas of Valtellina. The first site in Postalesio is situatedin the vicinity of a forest and has a humid microclimate, while the other site inSassella is located in a simpler environment with a dry microclimate. In both areastwo vineyards were selected: one that was full of weeds and a second one withoutweeds. In the Postalesio area the development of weeds was observed for manyyears, its composition is diversified and weeding is accurate, while in the Sassellaarea the growth of weeds is more recent with a more trivial composition. Differentbiodiversity indexes (Index of Shannon-Weaver H', the Hill's numbers: N0,N 1' D, N2, N inf, Index of Pielou J') and of similarity (Si:irensen's index QS) havebeen applied to the data. On the whole 59 species of Heteroptera were collectedbelonging to 12 families. The highest number of species and indexes of biodiversitywere found in the vineyard in Postalesio with weeds in 1997; the presenceof the forest and the diverse flora have favoured the biocenosis of Hemiptera. Inthe Sassella vineyard with weeds, whose vegetation has become richer during thestudy, the indices of biodiversity have shown a constant increase from '97 to '99.In the same area the flora that has taken over in the weed-free vineyard has ledto a biodiversity comparable to the one with weeds during the first year, whileafter two years the situation worsened. In the other weed-free vineyard no Heteropterahave been found.
Keywords: Heteroptera; biodiversity; vineyards; Valtellina